Problem-Based Learning Mathematics Modules: Their Impact on Students’ Mathematical Problem-Solving Performance - Mutiara Pertiwi; Yerizon; Ali Asmar; Yarman (Postgraduate, University of Mataram, 2026)
This research aims to develop a mathematics teaching module based on the Problem-Based Learning model to improve the mathematical problem-solving abilities of eleventh-grade students. Using the Plomp development model, the research was conducted through the initial investigation, prototyping, and assessment stages. The module was validated by experts in mathematics education, language, and educational technology, resulting in an average validity score of 3.56 (categorized as